Managing and Developing Communities, Festivals and Events - Jepson, Allan; Clarke, Alan.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2016)
The different stages of a festival's evolution provide a plethora of opportunities for us to better understand our culture, the relationships we build, what we value in our culture and our communities, and how we socialize and interact with one another. Managing and Developing Community Festivals and Events brings together community festival and event research from nine different countries. It critically explores how festivals and their communities develop and impact upon one another. The chapters focus on a wide range of festivals such as food and culinary festivals, art events, religious pilgrimage and feast festivals, as well as a variety of diverse themes such as joy, civil unrest, preservation of cultures and authenticity. .
Keywords: Business; Management; Leadership; Project management; Operations research; Decision making; Business ethics; Industrial management -- Environmental aspects; Business and Management; Business Ethics; Management; Project Management; Corporate Environmental Management; Business Strategy/Leadership.; Operation Research/Decision Theory; Electronic books